Ash melting behaviour of wheat straw blends with wood and reed. (August 2018) - Link, Siim; Yrjas, Patrik; Hupa, Leena
Abstract: Combustion of fuel blends is becoming more important. During combustion, interactions between ash-forming elements and compounds of different fuel blends can occur. Blending without sufficient knowledge and analysis can easily lead to operational problems, such as slagging, fouling and corrosion. Focus in our study is on the ash behaviour of wheat straw pellets blended with reed ( Phragmites australis ), wood pellets, and Douglas fir wood chips. The standard method (procedure) of CEN/TS 15370 and STA or simultaneous thermal analysis (thermogravimetric analysis (TGA) coupled with differential thermal analysis (DTA)) were applied to characterize the ash behaviour of the fuel blends studied. The ash melting behaviour of the blend of fuels depends not only on the composition, but also on the content of mineral matter of a single fuel. Low melting eutectics are possible when the K and/or Si-containing fuels are blended. Graphical abstract: